HUBUNGAN PATIENT CENTERED CARE DENGAN KEPUASAN PASIEN RAWAT INAP RSUD PANEMBAHAN SENOPATI BANTUL - Tia Aggeng Kirana; Nagita Setyaning Ratri; Susilowati; Edi Sampurno Ridwan (LPPM Universitas Awal Bros, 2026)
Patient satisfaction is the assessment made by patients and their families regarding the services provided by healthcare professionals in the hospital. Patient-Centered Care (PCC) is a new paradigm in healthcare services that places the patient at the center of care. PCC is not merely about emphasizing technology, but rather about recognizing the importance of interpersonal interactions. This study aims to analyze the relationship between the implementation of PCC and the satisfaction of hospitalized patients. The method used was quantitative with a cross-sectional design, involving 111 patients at Panembahan Senopati Bantul Regional General Hospital, selected using proportionate random sampling. The data collection techniques in this study involved the use of Patient-Centered Care and patient satisfaction questionnaires. Data analysis was conducted using the Pearson Correlation statistical test. The results showed a relationship between Patient-Centered Care (PCC) and inpatient satisfaction at Panembahan Senopati Bantul Regional General Hospital, with a p-value of 0.015 and a correlation coefficient of 0.230, indicating a positive but weak relationship. In conclusion, there is a relationship between Patient-Centered Care and patient satisfaction in the inpatient wards of Panembahan Senopati Bantul Regional General Hospital.